2021
DOI: 10.22159/ijap.2021.v13s4.43865
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antidiabetic Screening of Kabau (Archidendron Bubalinum (Jack) I. C Nielsen) Seeds

Abstract: Objective: Study described the screening potential antidiabetic activity of kabau seed extract and fraction. Methods: The powdered crude drugs weighing 1349.32 grams were extracted with a solvent with solvents with escalating polarity by using soxhletation. The solvents used were n-hexane, ethyl acetate, and 96% ethanol. Screening activity using three variations on doses on the three extracts using the glucose test tolerance method, then the alloxan induction and high-fat feed induction testing methods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Based on chemotaxonomy, plants in the same family and genus contain compounds with the same chemical structure framework, so they have the potential to have the same biological activity [5,6]. The study conducted by [7] show that Kabau seeds had antidiabetic activity and showed that ethanol extract at a dose of 250 mg/kg BW was better with the glucose tolerance test method, with alloxan induction animal models and high-fat feed induction. The methanol fraction derived from 96% ethanol extract gave a good decrease in blood sugar levels in the screening method with the glucose tolerance test.…”
Section: Introductionmentioning
confidence: 99%
“…Based on chemotaxonomy, plants in the same family and genus contain compounds with the same chemical structure framework, so they have the potential to have the same biological activity [5,6]. The study conducted by [7] show that Kabau seeds had antidiabetic activity and showed that ethanol extract at a dose of 250 mg/kg BW was better with the glucose tolerance test method, with alloxan induction animal models and high-fat feed induction. The methanol fraction derived from 96% ethanol extract gave a good decrease in blood sugar levels in the screening method with the glucose tolerance test.…”
Section: Introductionmentioning
confidence: 99%